Analisis Citra Satelit Himawari 8/9 Terkait Kejadian Hujan Es Di Wilayah Klaten Tanggal 21 Oktober 2021 - Sanjaya, Wulung; Amri, Syaiful (JFT: Jurnal Fisika dan Terapannya, 2022)
One of the extreme phenomena that often occurs is hail, hail can occur because when water vapor condenses it turns into ice particles due to the low air temperature factor. Hail includes local rain which covers an area of 5-10 km, and lasts a maximum of 10 minutes. On October 21, 2021, there was hail in Jogonalan Klaten. The incident occurred at around 14.18 WIB. By using Himawari-8 satellite data reference which was analyzed using the SATAID application and UV wind data obtained from the Copernicus web and processed with OpenGrADS software. Then as other supporting data used cloud top temperature data with band 13 himawari 8 which was processed using time series and also air lability data from the web weather.uwyo.edu. From the four data, it will be obtained that the formation of cumulonimbus clouds in the area around Klaten and Jogja as an indication of hail is strengthened by the convergence pattern in the northern region of the island of Java, precisely Central Java which causes a slowdown in the air mass that forms convective clouds which is the cause of hail in Klaten Regency. . This is reinforced by the results of the analysis of the cloud top temperature which reached -18°c.